Rivastigmine Patch in Chinese Patients with Probable Alzheimer's disease: A 24‐week, Randomized, Double‐Blind Parallel‐Group Study Comparing Rivastigmine Patch (9.5 mg/24 h) with Capsule (6 mg Twice Daily). (25th March 2016) - Zhang, Zhen‐Xin; Hong, Zhen; Wang, Yan‐Ping; He, Li; Wang, Ning; Zhao, Zhong‐Xin; Zhao, Gang; Shang, Lan; Weisskopf, Marianne; Callegari, Francesca; Strohmaier, Christine
Summary: Aims: To compare the once‐daily rivastigmine patch 9.5 mg/24 h (10 cm 2 ) versus twice‐daily capsule (12 mg/day) in Chinese patients with probable Alzheimer's disease (AD) (mini‐mental state examination [MMSE] scores of 10–20). Methods: The primary objective was to demonstrate the noninferiority of patch to capsule in Alzheimer's Disease Assessment Scale‐Cognitive subscale (ADAS‐Cog) change from baseline to 24 week. Secondary endpoints included cognition (MMSE), overall clinical response (Alzheimer's Disease Cooperative Study‐Clinical Global Impression of Change [ADCS‐CGIC]), activities of daily living (Alzheimer's Disease Cooperative Study‐Activities of Daily Living [ADCS‐ADL]), behavior (Neuropsychiatric Inventory [NPI‐12]), and safety. Results: Similar cognitive improvement was observed in both patch (n = 248) and capsule (n = 253) groups. Statistical noninferiority for ADAS‐Cog was not established (least‐square means difference, 0.1; 95% confidence interval, −1.2; 1.5). Considering all efficacy parameters into account, both treatments showed similar performance at Week 24. Treatment‐related adverse events (AEs) were lower for patch (39.7%) compared with capsule (49.8%). Application site pruritus was reported in 10.9% of patients receiving patch; most cases were mild. Gastrointestinal AEs including nausea, vomiting, and diarrhea occurred less frequently in the patch group (15.8% vs. 28.7%). Conclusion: Rivastigmine patch 9.5 mg/24 h is effective and well tolerated in Chinese patients with probable AD.